AUDIT OF SHARP WEAPON DEATHS IN METROPOLIS OF KARACHI -AN AUTOPSY BASED STUDY - Mirza, Farhat Hussain; Hasan, Qudsia; Memon, Akhtar Amin; Adil, Syeda Ezz-e-Rukhshan (Journal of Ayub Medical College Abbottabad, 2010)
Background: Sharp weapons are one of the most violent and abhorrent means of deaths. This study assesses the frequency of sharp weapon deaths in Karachi. Methods: This was a cross sectional study, and involves the deaths by sharp weapons autopsied in Karachi during Mar 2008-Feb 2009. Results: This study reports that the frequency of sharp weapon deaths in Karachi is similar to some other studies conducted in different regions of Pakistan, yet it is very high as the population of Karachi is way more than any other metropolis of Pakistan. Our study reported that out of 2090 medico-legal deaths in Karachi during the study period, 91 deaths were due to sharp weapons, including 73 (80.2%) males and 18 (19.8%) females. 100% of the deaths were homicides, so none were suicides. Deaths were more frequent in age group ranging from 20-39 years (59.3 %). Conclusion: Sharp weapon deaths continue to be a means of quite a number of deaths in Karachi. Such violence depicts intolerant and frustrated nature of the citizens. Keywords: Autopsy, homicide, sharp weapon, death